Avaliação de oxigenador de membrana infantil em ovinos - Finoti, Renata Geron (2011)
To analyze the security and efficacy of a new membrane oxygenator, the so-called OXM 1500. Methods: From May 2005 to September 2006, six sheep of Santa Inês breed (5 male and 1 female, respectively) were studied. The average body weight was 14.1 (±5) kg, body surface 0.6 (±0.2) m2 and a mean age 3.8 (±1.5) months. All of them were submitted to extracorporeal circulation (CEC) with evaluation at 10, 30, 60, 120, 180 and 240 minutes. The following values were obtained: values of oxygen transference (TTO2) and carbon dioxide transference (TTCO2), haemoglobin (HBS) and free haemoglobin (HBL), the score of platelets and of leucocytes, and heat transference rate. Results: TTO2 and TTCO2 were adequate. Lesion of the majority formed blood elements was insignificant; there no modifications in HBS, HBL levels; platelets and leucocytes decreased over time. Heat exchange was effective (p ≤ 0.05). Conclusions: The membrane OXM 1500 infant oxygenator, tested in sheep, showed adequate oxygenation capacity, CO2 removal capacity, and small alteration of haemoglobin and platelets without significant decrease of leucocytes, as expected. Heat exchanger connected to the oxygenator was efficient in temperature changes.